Correlation of neuropathy target esterase activity with specific tritiated di-isopropyl phosphorofluoridate-labelled proteins. - Thomas, T C (1989)
Neuropathy target esterase (NTE) is a membrane-bound carboxylesterase activity that has been proposed as the target site for initiation of organophosphate-induced delayed neuropathy. This activity is identified by its resistance to treatment with Paraoxon and sensitivity to co-incubation with Paraoxon and Mipafox. Sucrose-density-gradient centrifugation of membrane-associated proteins isolated from chick-embryo brains identified three proteins, Mr 161,000, 116,500 and 103,000, that were labelled with [3H]di-isopropyl phosphorofluoridate in an NTE-like manner and that co-migrated with NTE. The 161,000-Mr and 116,500-Mr proteins were identified in both adult and embryo brain. One or both of these proteins may therefore contribute to the activity defined as NTE. In addition, a 61,000-Mr protein was identified that does not comigrate with NTE, but that was labelled with [3H]di-isopropyl phosphorofluoridate in a Paraoxon-resistant and Mipafox-sensitive manner. The effect of Mipafox on labelling, however, was reversibly blocked by co-incubation with Paraoxon. This protein, therefore, is not NTE, but has the necessary inhibitor-sensitivity to be the target site for organophosphate-induced delayed neuropathy.